Participating in a food-assisted maternal and child nutrition and health program in rural Guatemala alters household dietary choices - Jensen Madrigal, Melissa Lorena (2016)
Background: Food assistance programs may alter food choices, but factors determining households! decisions regarding food acquisition, preparation, and consumption in the context of food aid are not well understood. Objective: This study aimed to understand how the Programa Comunitario Materno Infantil de Diversificacion Alimentaria ´ (Mother–Child Community Food Diversification Program; PROCOMIDA), a food-assisted maternal and child health and nutrition program in rural Alta Verapaz, Guatemala, altered household food choices. Methods: We conducted semistructured interviews and focus groups with 63 households in 3 participating (n = 32 households) and 3 control (n = 31) villages. A last-day food recall (without estimating quantities) and food-frequency questionnaire that used food cards assessed dietary choices. Qualitative analysis used thematic a priori and emergent coding; food group consumption frequencies were analyzed by using 2-level, logistic, mixed modeling, and chi-square testing while accounting for community clustering. Results: Compared with control households, PROCOMIDA changed household food choices through a combination of providing food resources (with monthly food rations) and new knowledge and skills related to health and food (in the program!s behavior change communication component) while reinforcing existing knowledge and beliefs. PROCOMIDA families consumed rice, red beans, and oil more frequently than did control families (differences of 2.20 (P < 0.001), 2.68 (P < 0.001), and 1.64 (P = 0.038) times/wk, respectively); these foods were in the rations. PROCOMIDA families also ate chicken, local plants, and some vegetables more frequently. The importance of these foods was emphasized in the behavioral change communication component; these foods may have been more accessible because provision of food rations freed resources. Conclusion: Our findings suggest that if a program provides food free of cost to rural indigenous families in the context of a maternal and child nutrition and health program, it may be important to include a well-designed behavioral change communication component to improve household food choices